Analysis of the Implementation of the Syirkah Contract on Nia Fiqih Muamalah Cake from the Perspective of Gowa Regency, South Sulawesi Province - Mumtihani, Andi Fakhriyah; Wahab, Abdul; Kara, Muslimin (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
The research investigates the implementation of the syirkah contract at Nia Cake in Gowa Regency, South Sulawesi, focusing on its mechanisms, obstacles, and perspectives from muamalah fiqh. Using a qualitative descriptive approach, data was collected through observations, interviews with managers and capital providers, and documentation from Islamic economics experts. Primary data stemmed from field research, while secondary data supported the findings. The study reveals that the syirkah contract begins with both oral and written agreements. The manager educates capital owners about the contract, agreeing on a 50% profit-sharing model, with losses shared equally. All terms are documented in a formal investment agreement. Trust is emphasized as a core principle among partners. From the muamalah fiqh perspective, two types of contracts are utilized: syirkah mudharabah and syirkah inan, both compliant with sharia law. However, challenges persist in educating potential non-Muslim investors about syirkah concepts and finding suitable capital providers. Additionally, the absence of a halal certificate for products complicates matters. The implications of this research suggest that it enhances understanding of syirkah mechanisms within small and medium enterprises (SMEs) and offers practical recommendations for businesses to adopt syirkah contracts to improve access to capital and foster economic growth while raising awareness of Islamic economic principles.